Quantitative Analysis of the Sources of Construction Waste. (20th October 2014) - Fadiya, Olusanjo O.; Georgakis, Panos; Chinyio, Ezekiel
Abstract : The construction industry is traditionally environmentally unfriendly. The environmental impacts of construction waste include soil contamination, water contamination, and deterioration of landscape. Also, construction waste has a negative economic impact by contributing additional cost to construction due to the need to replace wasted materials. However, in order to mitigate waste, construction managers have to explore management options, which include reduction, recycling, and disposal of wastes. Reduction has the highest priority among the waste management options but efficient reduction cannot be achieved without adequate identification of the sources of waste. Therefore, the purpose of this paper is to present a study that was carried out on the contribution rates of nine identified sources of construction waste. Establishing the contribution rates of different waste sources will enhance knowledge-based decision-making in developing appropriate strategy for mitigating construction waste. Quantitative research method, using survey questionnaire, was adopted in this study to assess the frequency and severity of contribution of the sources of waste. As one of the findings of the study, residual waste such as material off-cuts was identified as the highest contributor to construction waste. This study consequently demonstrated that waste has a significant contribution to the cost of construction.